Acoustooptic Diffraction of Three-Color Radiation on a Single Acoustic Wave - V. M. Kotov; S. V. Averin (International Journal of Optics)
Bragg diffraction which provides effective acoustooptic interaction of three-color radiation with a single acoustic wave at a high frequency of sound is proposed and tested in a single crystal of paratellurite at the wavelengths of λ= 0.488, 0.514, and 0.633 μm. Maximal diffraction efficiency of radiation with λ=0.633 μm at acoustic frequency of 150 MHz is 88% and that with λ= 0.488 μm and λ=0.514 μm is 60%. In diffraction efficiency range from 0 to 40% the dependence of all beams on acoustic power is the same.